2010
DOI: 10.1159/000321681
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Brain Creatine Kinase Activity in Huntington’s Disease

Abstract: Background: Huntington’s disease (HD) is associated with impaired energy metabolism in the brain. Creatine kinase (CK) catalyzes ATP-dependent phosphorylation of creatine (Cr) into phosphocreatine (PCr), thereby serving as readily available high-capacity spatial and temporal ATP buffering. Objective: Substantial evidence supports a specific role of the Cr/PCr system in neurodegenerative diseases. In the brain, the Cr/PCr ATP-buffering system is established by a concerted operation of the brain-specific cytosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…63 In addition, we also found that a subunit of complex II (succinate dehydrogenase), SDHA, subunits of complex III (cytochrome bc 1), UQCRC1 and 2, and a component of cytochrome c oxidase, SCO2 (complex IV), were also less abundant in HD cortex relative to controls. Overall, the observed changes in the protein levels in HD brains are consistent with the current view of the mechanisms of mitochondrial dysfunction in HD, such as a decrease in the enzymes of pyruvate dehydrogenase complex (PDHC), 64 inhibition of the respiratory chain enzymes (described above), increased oxidative stress 65 (superoxide dismutase 1, SOD1, is increased), decrease in brain-specific creatine kinase (CKB), 66 and inhibition of mitochondrial protein import by mutant Htt 67 (TIMM44 and TIMM8A, components of presequence translocase-associated motor complex, PAM, are decreased). The observed changes in six family members of the motor protein kinesin and dynein and changes in abundance of mitochondrial fission factors MFF, MFN2, and FIS1 are also consistent with the idea that mutant Htt may dysregulate mitochondrial dynamics and trafficking.…”
Section: Discussionsupporting
confidence: 84%
“…63 In addition, we also found that a subunit of complex II (succinate dehydrogenase), SDHA, subunits of complex III (cytochrome bc 1), UQCRC1 and 2, and a component of cytochrome c oxidase, SCO2 (complex IV), were also less abundant in HD cortex relative to controls. Overall, the observed changes in the protein levels in HD brains are consistent with the current view of the mechanisms of mitochondrial dysfunction in HD, such as a decrease in the enzymes of pyruvate dehydrogenase complex (PDHC), 64 inhibition of the respiratory chain enzymes (described above), increased oxidative stress 65 (superoxide dismutase 1, SOD1, is increased), decrease in brain-specific creatine kinase (CKB), 66 and inhibition of mitochondrial protein import by mutant Htt 67 (TIMM44 and TIMM8A, components of presequence translocase-associated motor complex, PAM, are decreased). The observed changes in six family members of the motor protein kinesin and dynein and changes in abundance of mitochondrial fission factors MFF, MFN2, and FIS1 are also consistent with the idea that mutant Htt may dysregulate mitochondrial dynamics and trafficking.…”
Section: Discussionsupporting
confidence: 84%
“…Second, creatine kinase (CK) concentrations were significantly reduced in the cortex and cerebellum in mice treated with efavirenz [40]. A decrease in CK has been associated with neurodegenerative diseases [41]. Third, efavirenz causes a concentration-dependent mitochondriopathy in human hepatic cells by inhibiting complex 1 of the respirator chain [42].…”
Section: Introductionmentioning
confidence: 99%
“…These detrimental influences of hydrogen peroxide on functional activity of CK are supported by free radical inhibition of tissues specific CK presented by [22]. PCr and CK were found to be slightly decreased in skeletal muscles of mice with deficient cytosolic and mitochondrial CK activity [21]. In Alzheimer's disea se, amyloid beta-peptide which induces generation of free radicals is thought to inhibit the oxidative sensitive enzyme CK and therefore causes neurodegene ration [30].…”
Section: Resultsmentioning
confidence: 98%
“…Western blotting with the antibodies against CK isoenzyme using cell homogenate from HeLa cells identifies a single band of 43 kDa. Brain homogenates from Alzheimer's patients show a decrease of CK activity by 86%, whereas expression levels of the enzyme were down by 14 % [7,21]. Additional ly it was shown that the exposure of CK isoenzymes in rat tissues (brain, heart, and muscles) to xanthine and xanthine oxidase or hydrogen peroxide resulted in a significant decrease in the activities of CK in a dose dependent fashion [22].…”
Section: Resultsmentioning
confidence: 99%